AI-Integrated Cloud Systems: Enhancing Reliability through Predictive Maintenance - Raman Vasikarla, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Integrating Artificial Intelligence into cloud environments represents a paradigm shift in system reliability management. This article examines how AI-driven automation tools leverage machine learning algorithms, advanced monitoring techniques, and predictive analytics to anticipate and prevent system failures before they manifest as critical issues. By creating self-optimizing ecosystems that adapt to real-time challenges, AI integration minimizes downtime and streamlines resource allocation, resulting in enhanced operational efficiency. The transformative capabilities of AI extend beyond reactive maintenance to establish proactive frameworks that continuously evolve to address emerging threats. By strategically implementing these technologies, organizations can achieve unprecedented levels of system reliability while simultaneously reducing operational costs and creating more resilient cloud infrastructures.
Keywords: Cloud Reliability; Artificial Intelligence Integration; Predictive Maintenance; Self-Optimizing Systems; Resource Automation